A Two‐Spacecraft Study of Mars' Induced Magnetosphere's Response to Upstream Conditions. Issue 4 (5th April 2022) - Stergiopoulou, Katerina; Andrews, David J.; Edberg, Niklas J. T.; Halekas, Jasper; Lester, Mark; Sánchez‐Cano, Beatriz; Dimmock, Andrew P.; Gruesbeck, Jacob R.
Abstract: This is a two‐spacecraft study, in which we investigate the effects of the upstream solar wind conditions on the Martian induced magnetosphere and upper ionosphere. We use Mars Express (MEX) magnetic field magnitude data together with interplanetary magnetic field (IMF), solar wind density, and velocity measurements from the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission, from November 2014 to November 2018. We compare simultaneous observations of the magnetic field magnitude in the induced magnetosphere of Mars (| B |IM ) with the IMF magnitude (| B |IMF ), and we examine variations in the ratio | B |IM /| B |IMF with solar wind dynamic pressure, speed and density. We find that the | B |IM /| B |IMF ratio in the induced magnetosphere generally decreases with increased dynamic pressure and that a more structured interaction is seen when comparing induced fields to the instantaneous IMF, where reductions in the relative fields at the magnetic pile up boundary (MPB) are more evident than in the field strength itself, along with enhancements in the immediate vicinity of the optical shadow of Mars. We interpret these results as evidence that while the induced magnetosphere is indeed compressed and induced field strengths are higher during periods of high dynamic pressure, a relatively larger amount of magnetic flux threads the region compared to that available from the unperturbed IMF during low dynamic pressure intervals. Plain Language Summary: The solar wind input to the Martian system plays a decisive role in formulating the morphology of the near‐Mars plasma environment. Specifically, ion escape rates, the plasma boundary locations around the planet and the structure of the induced magnetosphere in general have been shown by numerous studies to be influenced by the upstream solar wind conditions. In this work, we use simultaneous measurements from MEX and MAVEN to probe the response of the Martian induced magnetosphere and upper ionosphere to different regimes of solar wind dynamic pressure, speed and density. We find that despite the stronger magnetic fields observed in the induced magnetosphere during periods of high solar wind dynamic pressure, when we compare these fields with the interplanetary magnetic field (IMF) measured simultaneously, we see in fact relative enhancements for low solar wind dynamic pressure. Key Points: MEX and MAVEN data are used to examine the response of Mars' induced magnetosphere to the solar wind We find that induced magnetic fields are enhanced relative to the IMF during intervals of lower dynamic pressure Comparing induced fields to the instantaneous IMF reveals more structure in the interaction region at high altitudes